PENGELOLAAN WAKAF BERBASIS PROFESIONALISME NAZHIR DI DESA BULO-BULO KABUPATEN JENEPONTO - Putra, Trisno Wardy; M, Riskayanti (Jurnal Ar-Ribh, 2021)
This study explores how the management and development of waqf in Bulo-Bulo Village, Jeneponto Regency. The research method used is qualitative by using interview instruments and documentation on the object of research, namely nazhir waqf in Bulo-Bulo Village. The results of this study conclude that the management and development of waqf in Bulo-Bulo is still simple with traditional management. Therefore, the role of the government in this case the Ministry of Religion must be even more active in socializing and fostering nazhir so that existing waqf can continue to develop and provide broad benefits to the social welfare of Muslims who are the majority population. Keywords: Waqf, Productive, Nazhir